70 years of foundation and development of orthopaedic–traumatology service in Ivano-Frankivsk region - Klepach, Mykola (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to the 70th anniversary of foundation and development Orthopedic and Traumatological Service of Ivano-Frankivsk region